2019
DOI: 10.29303/jpmpi.v1i2.270
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Profesionalissme Guru dalam Menulis Karya Ilmiah

Abstract: Salah satu bentuk profesionalisme guru adalah memiliki kemampuan menulis artikel ilmiah. Guru SMP 2 Sekotong pada umumnya belum memiliki wawasan yang cukup tentang kepenulisan ilmiah sehingga guru mengalami kesulitan dalam meningkatkan kemampuan profesionalnya dalam bidang kepenulisan. Tujuan kegiatan pengabdian pada masyarakat ini adalah meningkatkan kompetensi guru dalam menulis karya ilmiah. Metode yang digunakan adalah pendekatan konstruktivisme, pelaksanaan kegiatan dibagi menjadi dua kali yaitu pertama p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
2
0
6
Order By: Relevance
“…The purpose of writing articles published in a journal or other mass media in accordance with the provisions of the guidelines is for the author to produce scientific writing, which can be said to be scientific because it has gone through the correct process or procedure. Scientific papers can be grouped into two large parts, namely; firstly scientific papers originating from research results reports and secondly; is a scientific written work in the form of a review, review or scientific idea (Hadi et al, 2019).…”
Section: Jurnal Pengabdian Kepada Masyarakatmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of writing articles published in a journal or other mass media in accordance with the provisions of the guidelines is for the author to produce scientific writing, which can be said to be scientific because it has gone through the correct process or procedure. Scientific papers can be grouped into two large parts, namely; firstly scientific papers originating from research results reports and secondly; is a scientific written work in the form of a review, review or scientific idea (Hadi et al, 2019).…”
Section: Jurnal Pengabdian Kepada Masyarakatmentioning
confidence: 99%
“…Besides as career development, writing can be used as a suggestion for a teacher's self-development, because teachers have a lot of potential that can be developed through writing optimally. Further expressed by Al Hadi (2019) that the professional development of teachers in writing scientific papers aims to develop career positions, where the credit score is one of the selection requirements for career advancement. So it can be concluded that one type of teacher professional development activity is creating scientific papers in the form of articles and then publishing them through journal institutions as an output product from research results.…”
Section: Jurnal Pengabdian Kepada Masyarakatmentioning
confidence: 99%
“…Oleh karena itu, tim pengabdian kepada masyarakat program studi Pendidikan Bahasa Inggris Universitas Muhammadiyah Purworejo bermaksud untuk berbagi ilmu dengan dengan guru-guru SMA Negeri 1 Gombong untuk dapat mengembangkan kemampuan menyusun PTK dengan benar dan effektif serta mengembangkan kemampuan menulis artikel hasil Penelitian Tindakan Kelas. Kegiatan ini seperti yang dilakukan di banyak sekolah dalam upaya meningkatkan kompetensi profesional guru diantaranya (Nurlina et al, 2022, Thoharudin et al, 2021, Al Hadi et al, 2019, dan Handayani & Rukmana, 2020.…”
Section: Pendahuluanunclassified
“…Kebijakan tersebut diantaranya kewajiban guru untuk melakukan tugas sesuai bidangnya, serta memperoleh angka kredit yang dapat digunakan untuk meningkatkan jenjang karir (Sodiq et al, 2014). Pemberian angka kredit sebagai suatu upaya pemberian penghargaan secara lebih adil dan professional sehingga dapat meningkatkan kesejahteraan guru tersebut (Al Hadi et al, 2019;Nafi'ah, 2022).…”
Section: Pendahuluanunclassified